Genes and Conditions Controlling Mammalian Pre- and Post-implantation Embryo Development - Anifandis, G.; Messini, C.I.; Dafopoulos, K.; Messinis, I.E. (Current Genomics, 2015)
Embryo quality during the in vitro developmental period is of great clinical importance. Experimental genetic studies during this period have demonstrated the association between specific gene expression profiles and the production of healthy blastocysts. Although the quality of the oocyte may play a major role in embryo development, it has been well established that the post – fertilization period also has an important and crucial role in the determination of blastocyst quality. A variety of genes (such as OCT, SOX2, NANOG) and their related signaling pathways as well as transcription molecules (such as TGF-β, BMP) have been implicated in the pre- and post-implantation period. Furthermore, DNA methylation has been lately characterized as an epigenetic mark since it is one of the most important processes involved in the maintenance of genome stability. Physiological embryo development appears to depend upon the correct DNA methylation pattern. Due to the fact that soon after fertilization the zygote undergoes several morphogenetic and developmental events including activation of embryonic genome through the transition of the maternal genome, a diverse gene expression pattern may lead to clinically important conditions, such as apoptosis or the production of a chromosomically abnormal embryo. The present review focused on genes and their role during pre-implantation embryo development, giving emphasis on the various parameters that may alter gene expression or DNA methylation patterns. The pre-implantation embryos derived from in vitro culture systems (in vitro fertilization) and the possible effects on gene expression after the prolonged culture conditions are also discussed.
Keywords: DNA methylation